Developing a Statistical Method for Control Chart of the Individual Measurements - Mohammad Mehdi Movahedi; Abbas Raad; Majid Nili Ahmadabadi; Behzad Ghasemi (چشم‌انداز مدیریت صنعتی, 2018)
When the statistical distribution of products under study is not normal or symmetrical, in order to use the X control chart it cannot be expected that the process variability is timely detected. In this study, to improve the performance of X control chart, Generalized Lambda Distribution (GLD) was applied. To illustrate how to implement the proposed method, the data pertaining to tensile straights of eighteen aluminum plates were utilized and upper and lower limits of X control chart were calculated. Chi-Square test and Average Run Length (ARL) method were employed to ensure the obtained results and to accredit the proposed method, respectively. Due to the flexibility of this distribution, applying the proposed method could ensure that the process variability is discovered ahead of time.